{001} crystal face exposed anatase type titanium dioxide nanosheet as well as preparation method and application thereof

Anatase-type titanium dioxide nanosheets with high specific surface area and surface energy were prepared by hydrothermal reaction in hydrofluoric acid solution, which solved the problem of slow kinetics of magnesium ion embedding in magnesium ion batteries, and achieved high capacity and stable electricity Chemical properties, suitable for positive electrode materials for magnesium ion batteries and magnesium lithium mixed batteries.

CN119240786AActive Publication Date: 2025-01-03CHONGQING UNIV +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411429419.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-03
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

Due to the strong polarization effect of divalent magnesium ions, the kinetics of magnesium ions in the positive electrode material are slow, which limits its application in magnesium ion batteries, and the discharge capacity of existing electrode materials is insufficient.

Method used

The crystal surface exposed anatase titanium dioxide nanosheets are prepared by hydrothermal reaction with the titanium source in hydrofluoric acid solution, which improves its specific surface area and surface energy, and serves as the positive electrode material for magnesium ion battery and magnesium lithium mixed battery, and reduces the The diffusion energy barrier of magnesium ions promotes the storage and electrochemical behavior of magnesium ions.

Benefits of technology

The prepared anatase-type titanium dioxide nanosheets have high specific capacity, low diffusion energy barrier and high stability. They can maintain more than 75% of the battery capacity during repeated charging and discharging, and are suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240786A_ABST
    Figure CN119240786A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery material technologies, catalysis and sensors, in particular to a {001} crystal face exposed anatase type titanium dioxide nanosheet and a preparation method and application thereof. The method comprises the following steps: adding a titanium source into a hydrofluoric acid solution, mixing and stirring to obtain a reaction precursor; transferring the reaction precursor into a reaction kettle for hydrothermal reaction; and after the reaction is finished, cooling, separating, washing and drying to obtain the {001} crystal face exposed anatase type titanium dioxide nanosheet. The preparation process is simple and efficient, and the obtained anatase type titanium dioxide nanosheet is high in purity, large in specific surface area and high in surface energy and can be applied as a positive electrode material of a magnesium ion battery and a magnesium-lithium hybrid battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of battery material technology, catalysis and sensors, and in particular to an anatase-type titanium dioxide nanosheet with exposed {001} crystal planes, a preparation method and an application thereof. Background Art

[0002] Compared with mainstream lithium-ion batteries, rechargeable magnesium-ion batteries (MIBs) are considered to be one of the most promising technologies for large-scale applications due to their abundant magnesium reserves, low price, high theoretical volumetric energy density, low electrode potential, and higher safety. They have become candidate batteries for the post-lithium-ion battery era. Although magnesium-ion batteries have many potential advantages, the strong polarization effect of divalent magnesium ions hinders the rapid insertion / extraction of magnesium ions in the cathode material, and may even inhibit the reversible insertion of magnesium ions in the cathode material, resulting in strong polarization and poor electrochemical behavior during charging and discharging. This shortcoming still makes magnesium-ion batteries face severe challenges.

[0003] So far, research on magnesium rechargeable batteries has been limited to a few choices of electrode materials, such as vanadium oxide, chevron phase, molybdenum sulfide, manganese oxide, and transition metal silicates. However, the kinetically sluggish nature of the magnesium ion diffusion process limits the magnesium ion intercalation capacity of these materials. Titanium dioxide is a naturally abundant, non-toxic material that is easy to prepare and has high chemical stability. It has been widely studied in various fields such as photocatalysis and lithium-ion batteries. Anatase titanium dioxide with a tetragonal crystal structure is probably the most studied metal oxide. Given its wide application in lithium-ion batteries and sodium-ion batteries, anatase titanium dioxide is also considered to be a promising electrode material for magnesium-ion batteries. However, the discharge capacity of the magnesium / anatase titanium dioxide prototype system in magnesium-ion batteries is still insufficient for various applications. Summary of the invention

[0004] The purpose of the present invention is to provide anatase titanium dioxide nanosheet with exposed {001} crystal plane, a preparation method and application thereof. The preparation process is simple and efficient. The obtained anatase titanium dioxide nanosheet has high purity, large specific surface area and high surface energy, and can be used as a positive electrode material for magnesium ion batteries and magnesium-lithium hybrid batteries.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing anatase titanium dioxide nanosheets with exposed {001} crystal planes, the method comprising: adding a titanium source to a hydrofluoric acid solution and mixing and stirring to obtain a reaction precursor; transferring the reaction precursor to a reactor for a hydrothermal reaction; after the reaction is completed, cooling, separating, washing, and drying to obtain anatase titanium dioxide nanosheets with exposed {001} crystal planes.

[0006] Furthermore, 3-6 mL of a titanium source is added to every 0.3-1.6 mL of a hydrofluoric acid solution having a concentration of 47%; the titanium source includes tetrabutyl titanate, titanium tetrachloride or isopropyl titanate.

[0007] Furthermore, the temperature of the hydrothermal reaction is 100-200° C., and the hydrothermal reaction time is 16-24 hours.

[0008] Furthermore, the thickness of the obtained anatase titanium dioxide nanosheets with exposed {001} crystal planes ranges from 6 to 8 nm.

[0009] Furthermore, the separation method is centrifugation or filtration; the washing solvent is at least one of deionized water, anhydrous ethanol and acetone, and the product is washed with the washing solvent until the pH of the product is neutral; and the drying is at least one of forced air drying, natural drying, freeze drying and vacuum drying.

[0010] In a second aspect, the present invention provides an anatase titanium dioxide nanosheet with an exposed {001} crystal plane, which is prepared by the above-mentioned method for preparing anatase titanium dioxide nanosheet with an exposed {001} crystal plane.

[0011] In a third aspect, the present invention provides an application of anatase-type titanium dioxide nanosheet with exposed {001} crystal plane obtained by the method for preparing anatase-type titanium dioxide nanosheet with exposed {001} crystal plane as described above in a positive electrode material for a magnesium-based battery.

[0012] Beneficial effects of the present invention: The present invention uses hydrofluoric acid as a structure control agent for titanium dioxide nanosheets, and prepares anatase-type titanium dioxide nanosheets with exposed {001} crystal planes by a hydrothermal synthesis method. The obtained anatase-type titanium dioxide nanosheets have high purity, large specific surface area, and high surface energy, and can be used as positive electrode materials for magnesium ion batteries and magnesium-lithium hybrid batteries. The preparation method is simple, has good repeatability, is easy to operate, and is expected to be applied to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a flow chart of a method for preparing anatase titanium dioxide nanosheets with exposed {001} crystal planes provided in an embodiment of the present invention.

[0014] Figure 2 This is a SEM image of anatase titanium dioxide nanosheet with exposed {001} crystal plane prepared in Example 1 of the present invention.

[0015] Figure 3 This is a SEM image of the positive electrode material prepared in the comparative example; Figure 4 This is the XRD pattern of the anatase titanium dioxide nanosheet with exposed {001} crystal plane prepared in Example 1 of the present invention.

[0016] Figure 5 The charge and discharge curves of anatase titanium dioxide nanosheets with exposed {001} crystal planes prepared in Example 1 of the present invention assembled into a rechargeable magnesium battery in an APC+LiCl electrolyte.

[0017] Figure 6 The figure is the charge-discharge curve of the anatase titanium dioxide nanosheets with exposed {001} crystal plane prepared in Example 1 of the present invention after being assembled into a rechargeable magnesium battery in APC electrolyte.

[0018] Figure 7 The cyclic voltammetry curve of the anatase titanium dioxide nanosheets with exposed {001} crystal plane prepared in Example 1 of the present invention assembled into a rechargeable magnesium battery in APC electrolyte.

[0019] Figure 8 This is the cycling curve of anatase titanium dioxide nanosheets with exposed {001} crystal plane obtained in Example 1 of the present invention assembled into a rechargeable magnesium battery in APC electrolyte. DETAILED DESCRIPTION

[0020] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.

[0021] In one embodiment, see Figure 1 As shown, the present invention provides a method for preparing anatase titanium dioxide nanosheets with exposed {001} crystal planes, the method comprising: adding a titanium source to a hydrofluoric acid solution and mixing and stirring to obtain a reaction precursor; transferring the reaction precursor to a reactor for a hydrothermal reaction; after the reaction is completed, cooling, separating, washing, and drying to obtain anatase titanium dioxide nanosheets with exposed {001} crystal planes.

[0022] The present invention successfully prepared anatase titanium dioxide nanosheets with {001} crystal plane exposed by combining hydrofluoric acid solution with hydrothermal synthesis reaction. By exposing the crystal plane with the highest surface energy of titanium dioxide, the larger specific surface area gives the material more magnesium ion adsorption sites and broad ion diffusion channels, thereby achieving the purpose of reducing the diffusion energy barrier of magnesium ions in the structure, promoting the storage of magnesium ions in the structure, and improving the battery capacity. The obtained anatase titanium dioxide nanosheets with {001} crystal plane exposed have high specific capacity, low diffusion energy barrier, and high stability. At 500 mAg -1After 1000 cycles under the current line, the specific capacity can still be maintained above 75%.

[0023] In a preferred embodiment, 3-6 mL of a titanium source is added to every 0.3-1.6 mL of a hydrofluoric acid solution having a concentration of 47%; the titanium source comprises tetrabutyl titanate, titanium tetrachloride or isopropyl titanate.

[0024] After adding the titanium source, the titanium ions in the reaction system coordinate with the fluoride ions to form stable complexes. These complexes are gradually converted into titanium dioxide nanosheets during the hydrothermal reaction. By adjusting the concentration of the hydrofluoric acid solution, the amount of titanium source added, and the conditions of the hydrothermal reaction (such as temperature, time, etc.), the morphology, size, and crystal structure of the product can be precisely controlled.

[0025] In a preferred embodiment, the temperature of the hydrothermal reaction is 100-220° C., and the hydrothermal reaction time is 16-24 hours.

[0026] At a lower hydrothermal reaction temperature, the crystal growth rate is slow, which may lead to low crystallinity or uneven morphology of the product. At an excessively high hydrothermal reaction temperature, although the crystal growth rate is accelerated, it may also induce unnecessary side reactions, such as crystal agglomeration or phase change, thereby affecting the performance of the product. Therefore, the temperature of the hydrothermal reaction is set to 100~220℃.

[0027] Similarly, the choice of reaction time is also based on the optimization of the crystal growth process. A shorter hydrothermal reaction time may not be enough to completely convert the titanium source into titanium dioxide nanosheets, or result in incomplete product morphology. Excessively long hydrothermal reaction time may increase energy consumption and cost, or even cause excessive crystal growth and performance degradation. Therefore, the hydrothermal reaction time is set to 16 to 24 hours.

[0028] By precisely controlling the temperature and time of the hydrothermal reaction, the hydrolysis and polycondensation of the titanium source can be further promoted, which is conducive to the formation of anatase titanium dioxide nanosheets with exposed {001} crystal planes. At the same time, the special definition of the hydrothermal reaction conditions also helps to improve the crystallinity, purity and stability of the product, so that it can show better performance in practical applications.

[0029] In a preferred embodiment, the thickness of the obtained anatase titanium dioxide nanosheets with exposed {001} crystal planes is in the range of 6 to 8 nm.

[0030] First, thinner nanosheets mean a larger specific surface area, which is beneficial for providing more active sites and enhancing its performance as an electrode active material. At the same time, thin nanosheets are also conducive to the transport and separation of charges, further improving its electrical performance.

[0031] Secondly, the {001} crystal plane is one of the most active crystal planes in anatase titanium dioxide, with higher surface energy and stronger adsorption capacity. Therefore, by exposing this crystal plane, the activity and selectivity of titanium dioxide nanosheets in the reaction are significantly improved.

[0032] In addition, nanosheets with a thickness of 6 to 8 nm also have good stability and dispersibility, which is conducive to maintaining their excellent performance in practical applications and avoiding phenomena such as agglomeration or precipitation.

[0033] In order to obtain nanosheets within this thickness range, the conditions of the hydrothermal reaction need to be finely controlled. In addition to the temperature and time ranges mentioned above, factors such as the concentration of the titanium source, the amount of hydrofluoric acid used, the pH value of the reaction solution, and the post-reaction treatment process need to be considered. By comprehensively considering these factors, the thickness of the nanosheet can be precisely controlled.

[0034] In a preferred embodiment, the separation method is centrifugation or suction filtration. The washing solvent is at least one of deionized water, anhydrous ethanol and acetone, and the product is washed with the washing solvent until the pH of the product is neutral. The drying is at least one of forced air drying, natural drying, freeze drying and vacuum drying.

[0035] First, in the separation step, two methods, centrifugation or filtration, are used. Centrifugation is a method that uses centrifugal force to separate the reaction product from the solution. It is suitable for processing a large amount of products and can complete the separation process quickly. Filtration is a method that uses negative pressure to form a filter cake on the filter paper and then separate it from the solution. It is suitable for processing products with high viscosity or fine particles. Both methods can effectively separate titanium dioxide nanosheets from the reaction solution, providing convenience for subsequent processing.

[0036] Secondly, in the washing step, at least one of deionized water, anhydrous ethanol and acetone is selected as the washing solvent. These solvents have good solubility and volatility, and can effectively remove residues and impurities on the surface of the product. By washing multiple times until the pH value of the product is neutral, the purity and stability of the product can be ensured. During the washing process, it is necessary to pay attention to controlling the number of washings and the washing time to avoid unnecessary loss or damage to the product.

[0037] Finally, in the drying step, a variety of drying methods are provided for selection, including at least one of forced air drying, natural drying, freeze drying and vacuum drying. Forced air drying is a method of using hot air to quickly evaporate the water or solvent in the product, which is suitable for processing a large amount of products and requiring drying time. Natural drying is a method of placing the product in a well-ventilated environment for natural air drying, which is suitable for situations where there are no strict requirements for drying time and the output is not large. Freeze drying is a method of removing moisture from the product by sublimation under reduced pressure after freezing the product at low temperature, which is suitable for processing products that are volatile or heat-sensitive. Vacuum drying is a method of heating and drying the product under vacuum conditions, which can accelerate the drying process and reduce the contact time of the product with oxygen, thereby protecting the performance of the product.

[0038] In summary, by selecting appropriate separation, washing and drying methods, the prepared anatase titanium dioxide nanosheets with exposed {001} crystal planes were effectively post-treated to ensure their purity and stability, providing high-quality samples for subsequent characterization and application.

[0039] In one embodiment, the present invention further provides an anatase titanium dioxide nanosheet with exposed {001} crystal plane, which is prepared by the above-mentioned method for preparing anatase titanium dioxide nanosheet with exposed {001} crystal plane.

[0040] In one embodiment, the present invention further provides an application of anatase titanium dioxide nanosheet with exposed {001} crystal plane obtained by the method for preparing anatase titanium dioxide nanosheet with exposed {001} crystal plane as described above in a positive electrode material for a magnesium-based battery.

[0041] Furthermore, the present invention also provides a method for preparing a positive electrode sheet, comprising the following steps: 1) The prepared anatase titanium dioxide nanosheets with exposed {001} crystal planes were used as the positive electrode active material, and the positive electrode active material was ground and uniformly mixed with a binder and a conductive agent in a mass ratio of 7:2:1 to obtain a mixed material. The mixed material was then added to NMP (N-methylpyrrolidone) and stirred for 8-12 h to obtain a positive electrode material slurry.

[0042] 2) Apply the positive electrode material slurry on carbon paper or molybdenum foil, put it in a vacuum oven, and dry it at 80-100°C for 10-12 hours to obtain a positive electrode sheet. Finally, cut the positive electrode sheet into a disc with a diameter of 10 mm and put it in a glove box for standby use.

[0043] Magnesium-based battery assembly, the positive electrode plate is made of anatase-type titanium dioxide nanosheet with exposed {001} crystal plane obtained by the preparation method of the present invention as the positive electrode active material, and the negative electrode uses magnesium foil with a purity of 99.9% or 99.99%. The magnesium foil needs to be surface polished before use. Use sandpaper with a molybdenum of 1200 or above to polish it until the surface is smooth and scratch-free. Then put it in anhydrous alcohol for ultrasonic cleaning, and finally put it in a vacuum oven to dry to obtain the negative electrode.

[0044] The electrolyte is reasonably selected according to the type of assembled battery. For example, when the assembled battery is a magnesium ion battery, the electrolyte is a commercial APC electrolyte. When the assembled battery is a magnesium-lithium hybrid battery, the electrolyte is 0.4 M LiCl + 0.4 M APC mixed electrolyte. The preparation method is as follows: weigh 0.2~1 g of lithium chloride (LiCl) and add it to 10~20 ml of commercial APC electrolyte, stir for more than 10 hours to obtain a mixed electrolyte.

[0045] It should be noted that the battery consists of a positive electrode, a negative electrode, and an electrolyte as well as a separator and a current collector. The separator is a glass fiber separator known in the art, and the current collector is a non-corrosive current collector such as carbon paper. The battery assembly and electrolyte configuration are carried out in a glove box filled with argon gas, with the water content and oxygen content maintained below 0.01ppm.

[0046] The following is an explanation with reference to specific examples.

[0047] Embodiment 1, a method for preparing anatase titanium dioxide nanosheet with exposed {001} crystal plane, the method comprising the following steps: S1, add 5 mL of tetrabutyl titanate solution to 0.6 mL of 47% hydrofluoric acid solution, mix and stir for 1 hour to obtain a reaction precursor.

[0048] S2, transferring the reaction precursor to a reactor for hydrothermal reaction, the hydrothermal reaction temperature is 180° C., and the hydrothermal reaction time is 12 hours.

[0049] S3, after the reaction is completed, cooling, separation, washing and drying are performed to obtain anatase titanium dioxide nanosheets with exposed {001} crystal planes.

[0050] The separation method is centrifugation, and the number of centrifugation is 3 to 6 times. The product is washed with deionized water / anhydrous ethanol / acetone, and the product is washed with the washing solvent until its pH is neutral. The product is initially dried by forced air drying for 1 to 3 hours to remove moisture, and then further dried by vacuum drying, with the temperature set at 80 to 100°C and the time set at 12 to 18 hours to further dry the product.

[0051] Comparative Example: A method for preparing anatase titanium dioxide nanosheets with exposed {001} crystal planes is provided, wherein the main steps are the same as those of the above embodiment, except that the added titanium source is different. Specifically, 5 mL of isopropyl titanate is added to 0.6 mL of a 47% hydrofluoric acid solution and mixed and stirred to obtain a reaction precursor; the reaction precursor is transferred to a reactor for a hydrothermal reaction.

[0052] The obtained product was subjected to SEM analysis. Figure 2 , indicating that the obtained product has a regular morphology, a nanosheet structure, a rectangular outline (side length of 40~60 nm), and a large specific surface area.

[0053] The product obtained in the comparative example Figure 3 As shown, the obtained product is a relatively large block-shaped polyhedral crystal, and its specific surface area is smaller than that of the product obtained in Example 1.

[0054] The product obtained in Example 1 was subjected to XRD analysis, and the results are shown in Figure 4 The obtained structure is a complete, smooth, uniform flaky anatase titanium dioxide with exposed {001} crystal planes. The main peak corresponds clearly to the standard card and there are no impurity peaks.

[0055] In order to verify the performance of the product obtained in Example 1, the anatase-type titanium dioxide nanosheet with exposed {001} crystal plane obtained in Example 1 was used as the positive electrode active material to prepare the positive electrode sheet, and then the magnesium-based battery was assembled. The magnesium-based battery assembly specifically includes the following steps: 1) The prepared anatase titanium dioxide nanosheets with exposed {001} crystal planes were used as positive electrode active materials. The positive electrode active materials were ground and uniformly mixed with a binder and a conductive agent in a mass ratio of 7:2:1 to obtain a mixed material. The mixed material was then added to NMP (N-methylpyrrolidone) and stirred for 12 h to obtain a positive electrode material slurry.

[0056] 2) Apply the positive electrode material slurry on carbon paper or molybdenum foil, put it in a vacuum oven, and dry it at 100°C for 12 hours to obtain a positive electrode sheet. Finally, cut the positive electrode sheet into a disc with a diameter of 10 mm and put it in a glove box for standby use.

[0057] 3) Prepare electrolyte. There are two types of electrolytes: magnesium ion electrolyte and magnesium-lithium dual salt mixed electrolyte. The magnesium ion electrolyte is a commercial APC electrolyte. The magnesium-lithium mixed electrolyte is 0.4 M LiCl + 0.4 M APC electrolyte. The preparation method is as follows: weigh 0.2 g of lithium chloride (LiCl) and add it to 10 mL of commercial APC electrolyte. Stir for more than 10 hours to obtain a mixed electrolyte.

[0058] 4) Prepare the negative electrode. Use 1200-grit sandpaper to polish a 0.1mm thick and 11mm diameter magnesium foil disc. After polishing until there are no scratches and it is bright, put it into anhydrous ethanol for ultrasonic cleaning. Then put it into a vacuum oven and dry it at 60°C for 12 hours. Finally, transfer it to the glove box for standby use.

[0059] 5) Using a battery shell, the separator and the positive electrode sheet, the negative electrode sheet and the electrolyte prepared by the above method are conventionally assembled to obtain a magnesium-based battery.

[0060] The electrochemical performance of the obtained magnesium-based battery was tested, and the results are shown in Figures 5 to 7 .

[0061] Depend on Figure 5 It can be seen that the cathode material prepared in Example 1 has a specific capacity of up to 280 mAh / g in a double salt electrolyte and has a distinct charge and discharge platform. The current density used in the test is 50 mA / g.

[0062] Depend on Figure 6 It can be seen that the positive electrode material prepared in Example 1 has a specific capacity of 67 mAh / g in a pure magnesium electrolyte at a low current.

[0063] Depend on Figure 7 It can be seen that the CV curve of the positive electrode material prepared in Example 1 is tested at a voltage of 0.1mv. Figure 6 It can be seen that there is a more obvious redox peak in the pure magnesium electrolyte.

[0064] Depend on Figure 8 It can be seen that the cycle curve of the positive electrode material prepared in Example 1 is tested at a current density of 200 mA / g. Figure 8 It can be seen that after 20 cycles, the specific capacity can still be maintained above 85%.

Claims

1. A method for preparing anatase-type titanium dioxide nanosheets with exposed {001} crystal planes, characterized in that: The method comprises: adding a titanium source into a hydrofluoric acid solution and mixing and stirring to obtain a reaction precursor; The reaction precursor is transferred to a reactor for a hydrothermal reaction; after the reaction is completed, the anatase titanium dioxide nanosheet with the {001} crystal plane exposed is obtained through cooling, separation, washing and drying.

2. The method for preparing anatase titanium dioxide nanosheets with exposed {001} crystal plane according to claim 1, characterized in that: Add 3-6 mL of titanium source to every 0.3-1.6 mL of 47% hydrofluoric acid solution; The titanium source includes tetrabutyl titanate, titanium tetrachloride or isopropyl titanate.

3. The method for preparing anatase titanium dioxide nanosheets with exposed {001} crystal plane according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100-220° C., and the hydrothermal reaction time is 16-24 hours.

4. The method for preparing anatase titanium dioxide nanosheets with exposed {001} crystal plane according to claim 1, characterized in that: The thickness of the obtained anatase titanium dioxide nanosheets with exposed {001} crystal planes ranges from 6 to 8 nm.

5. The method for preparing anatase titanium dioxide nanosheets with exposed {001} crystal plane according to claim 1, characterized in that: The separation method is centrifugation or filtration; The washing solvent is at least one of deionized water, anhydrous ethanol and acetone, and the product is washed with the washing solvent until the pH of the product is neutral; The drying is at least one of forced air drying, natural air drying, freeze drying and vacuum drying.

6. An anatase titanium dioxide nanosheet with exposed {001} crystal plane, characterized in that: The nanosheet is prepared by the method for preparing anatase-type titanium dioxide nanosheet with exposed {001} crystal plane as described in any one of claims 1 to 5.

7. Use of anatase-type titanium dioxide nanosheet with exposed {001} crystal plane obtained by the method for preparing anatase-type titanium dioxide nanosheet with exposed {001} crystal plane as claimed in any one of claims 1 to 5 in magnesium-based battery positive electrode materials, catalysis or sensors.

Citation Information

Patent Citations

  • Titanium dioxide nanoplate and synthesizing method thereof

    CN101462769A

  • Method for preparing single-crystal anatase titanium dioxide film

    CN101949054A

  • Method for preparing photoelectrocatalysis electrode material capable of efficiently degrading organic pollutants

    CN103132120A

  • Preparation method and application of anatase type TiO2 nanoflake

    CN104071833A

  • Rechargeable magnesium battery

    CN104538669A